Analisis Strategi Pemasaran Spotify Berdasarkan Marketing Mix 7P dalam Meningkatkan Brand Awareness, Loyalitas, dan Keputusan Berlangganan Premium: Studi Kasus Mahasiswa Institut Teknologi Del - Arika Purba; Citra Pardosi; Pavel Manurung; Cristin Siringoringo; Santi Agustina Manalu (Economic Reviews Journal, 2026)
This research analyzes the influence of Spotify's marketing strategy based on the 7P marketing mix in increasing brand awareness, loyalty, and Premium subscription decisions among students of Del Institute of Technology. The research background arises from the low conversion rate of free users to Premium despite Spotify's strong brand awareness. Using a mixed method, data was collected through a Likert scale questionnaire and in-depth interviews with selected respondents. The results showed that most of the 7P elements, such as product, place, physical evidence, and process, received high ratings, while price was the weakest factor because it was considered less affordable. Brand awareness and loyalty are in the high category, but the subscription decision is still hampered by the low perceived need before trying Premium services. The research also resulted in recommendations for new, more adaptive strategies, including flexible pricing schemes, academic thematic promotions, as well as the integration of learning support features specifically available to Premium users. Overall, Spotify's marketing strategy was found to have a positive effect, but adjustments to pricing, promotions, and benefits education are needed to increase the conversion of students into Premium subscribers.